One-pot construction of functionalized aziridines and maleimides via a novel pseudo-Knoevenagel cascade reaction. Issue 14 (23rd January 2020) - Lei, Jie; Song, Gui-Ting; He, Liu-Jun; Luo, Ya-Fei; Tang, Dian-Yong; Lin, Hui-Kuan; Frett, Brendan; Li, Hong-yu; Chen, Zhong-Zhu; Xu, Zhi-Gang
Abstract : Synthesis of functionalized aziridines, aziridinyl succinimides and maleimides via an Ugi, novel pseudo-Knoevenagel, ring expansion cascade reaction in one-pot. Abstract : An Ugi, novel pseudo-Knoevenagel, ring expansion cascade reaction was discovered and utilized for the synthesis of aziridinyl succinimides in one-pot. Subsequently, densely functionalized aziridines and maleimides have been designed and synthesized through similar cascade reactions. The target compounds were prepared by means of a mild reaction and a simple operation procedure, which could be applicable to a broad scope of starting materials. This series of novel cascade reactions generates opportunities for the tailored synthesis of a wide range of biologically active scaffolds through tuneable Ugi inputs. Discovery of compound 8i with comparable potency to sorafenib in liver cancer cell lines could provide a new avenue for liver cancer drug discovery.